¿Pacheco o Herrera? La construcción editorial de Versos (1619) - Ruiz Pérez, Pedro (El Colegio de México, 2021)
This study offers a complementary perspective on the textual problem of Herrera’s Versos. Instead of collating variants in the poems, it approaches the question from the material features of the book itself. It then takes into account the characteristics of the Sevillian printing press and the socio-cultural situation of the city. In the context of the data gathered in this way, it finally re-reads the statements made in the prologue. Doubts about Pacheco’s extensive editorial intervention increase when the significance and novelty of the presentation are taken into account, for they are aspects which can only be attributed to Herrera.